El derecho a la identidad de los hijos de las parejas del mismo sexo, procreados por técnicas de reproducción asistida - Bertha Rebeca, Guamán Atupaña (2021)
ABSTRAC This paper analyzes the sentence issued by the Ecuadorian constitutional court in case N° 184- 18-SEP-CC, focusing the analysis on the rights to the identity of the children of same-sex couples, procreated by assisted reproduction techniques. The specific case is about the request made by Nicola Susan Rothon and Helen Louise Bicknell to the Director of the Civil Registry so that they register their daughter Satya Amani with her two maternal surnames. Double maternity as a legal figure was not provided for in the Ecuadorian legal system because the Civil Registry, Identification, and Cedulation law in its article 32 established a requirement for the minor´s registration, the names, and surnames and nationality of the father and mother. Therefore, based on the fact that our legislation does not contemplate this possibility, being a family made up of two women by trade, they denied the minor two maternal surnames registration. Unit I refers to the right to identity of the child and adolescent, different doctrinal concepts about the child’s right to identity are disclosed according to the constitution, the code of childhood and adolescence, II, Assisted Human Reproduction Techniques from the ruling of the constitutional court N°. 184-2018-SEP-CC; We find doctrinal concepts and their characteristics and types of assisted reproduction techniques between why to resort to these methods, and thus we will analyze the well-known case “Satya” and its antecedent. In unit III, the incidence of Assisted Human Reproduction Techniques on the identity rights of children and adolescents. The right to know their biological parents, the right to maintain family relationships with biological parents, and, therefore, the consequences. The practical case of sentence N°. 184-2018-SEP-CC, issued by the Constitutional Court of Ecuador, authorized the registration of a minor in favor of her two mothers. Keywords; right to identity, reproduction techniques, double maternity, homo-parental family.Reviewed by: Mgs. Lorena Solís Viteri INGLISH PROFESSOR c.c.0603356783